Book review about: Silencing the Past. Power and the Production of the Past, by Michel-Rolph Trouillot (1995) - Axel Lazzari (Memoria Americana. Cuadernos de Etnohistoria, 2002)
Review of the book written by Michel-Rolph Trouillot (1995) titled Silencing the Past. Power and the Production of the Past. Boston, Beacon Press.